2011
DOI: 10.1007/s00436-011-2391-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Hysterothylacium aduncum (Nematoda: Raphidascaridae) from different fish caught off the Tunisian coast based on nuclear ribosomal DNA sequences

Abstract: Larval forms of the genus Hysterothylacium have been previously reported in teleost fish from the North African coasts of central Mediterranean Sea by morphological analysis. In the present study, samples identified morphologically as Hysterothylacium aduncum (n = 62), from Merluccius merluccius, Trachurus mediterraneus and Pagellus erythrinus from different geographical locations of the Tunisian coasts, were genetically characterised by sequences of the first (ITS-1), the 5.8S and second (ITS-2) Internal Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…Nucleotide sequences of L4 stage larvae of H. aduncum specimens isolated from three commercially important fish species caught off the Eastern Mediterranean cost are also shown to be effective in molecular identification at species level, using both ITS rDNA and mtDNA cox1 regions. Results indicated that the ITS rDNA sequences from our study are highly similar to those already submitted to GenBank in previous studies [1,19,26,42,[45][46][47]. We were not able to compare mtDNA cox1 sequences, as this is the first molecular study using mtDNA cox1 sequences in identification of H. aduncum.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Nucleotide sequences of L4 stage larvae of H. aduncum specimens isolated from three commercially important fish species caught off the Eastern Mediterranean cost are also shown to be effective in molecular identification at species level, using both ITS rDNA and mtDNA cox1 regions. Results indicated that the ITS rDNA sequences from our study are highly similar to those already submitted to GenBank in previous studies [1,19,26,42,[45][46][47]. We were not able to compare mtDNA cox1 sequences, as this is the first molecular study using mtDNA cox1 sequences in identification of H. aduncum.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies based on nucleotide sequences of ITS rDNA gene clearly demonstrated the effectiveness of this genetic marker in molecular identification of ascaridoid species [1,19,26,[39][40][41][42][43][44]. Nucleotide sequences of L4 stage larvae of H. aduncum specimens isolated from three commercially important fish species caught off the Eastern Mediterranean cost are also shown to be effective in molecular identification at species level, using both ITS rDNA and mtDNA cox1 regions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hysterothylacium constitutes a large number of described species, approximately 70, which have been recorded in marine fishes worldwide (Li, Gibson et al., ; MacKenzie et al., ; Pekmezci et al., ; Shamsi et al., ). In Mediterranean and North‐East Atlantic waters, H. aduncum (Rudolphi, 1802) is the most frequently reported species in many teleost fishes, but other species such as H. fabri (Rudolphi, 1819) Deardorff & Overstreet, 1980; H. corrugatum Deardorff & Overstreet, ; H. incurvum (Rudolphi, 1819) Deardorff & Overstreet, 1980; and H. petteri Sheenko, 1991 have also been recorded (Amor, Farjallah, Merella, Said, & Slimane, ; MacKenzie et al., ; Mattiucci et al., ; Ternengo, Levron, Mouillot, & Marchand, ). Up to 17 Hysterothylacium larval morphotypes have been described, based mainly on the anterior digestive tract and the caudal end of larvae, the first description in Australian marine waters being by Cannon ().…”
Section: Introductionmentioning
confidence: 99%
“…However, to date there has not been any study regarding molecular characterization of R. acus from fish caught off the Turkish waters. Recently, molecular techniques, using DNA sequencing of the nuclear ribosomal DNA spacers, have been proven to be particularly useful for the accurate identification of ascaridoid nematodes at the species level for eggs, larvae, and adults [5][6][7][8][9][10][11][12] . Nevertheless, before the present study, there had been no reports of characterizing the R. acus from the Turkish waters using well-defined internal transcribed spacers (ITS1 and ITS2) and 5.8S region sequence.…”
Section: Introductionmentioning
confidence: 99%